XML Schema Validation Using Java API for XML Processing - Jamal, Shene Jalil; Rahman, Chnoor M.; Abdulkarim, Mzhda S. (UKH journal of science and engineering, 2022)
Extensible Markup Language (XML) is a markup language that is developed to organize the structure of information in a text file. The data in XML formatted documents are represented by specifying a number of tags and determining the structural relationship between those tags. It has a simple structure and can be handled by any text editor. Therefore, XML formatted data is being commonly used to transfer and share data between different applications and organizations without having to convert the format of the data (Yang, 2019). In the XML world, “well-formed” and “valid” are the two most frequently used terms. A well-formed XML document is free from errors that can cause the document to not parse, such as: spelling, punctuation, grammar, and syntax errors. While in addition to having a well-formed markup, a valid XML must conform to a document type definition, this means the document must be semantically correct and matches a described standard of schemas and relationships (Appel, 2020).There are two standards of document type definition that can be used to validate an XML document, one is DTD or Document Type Definition which is used to identify the legal structure and names the legal elements of an XML document (Dykes and Tittel, 2011), and the other is XSD or XML Schema Definition. XSD is a diagrammatic representation that defines the valid structure of an XML document, it enables specifying the building blocks of an XML data set such as elements and attributes and their data types, number of child elements, fixed and default values of the elements and attributes that can appear in the documents (XML Schema Tutorial, 2020). In some applications the process of validating XML documents is combined with parsing the document. However, in some other cases the process of parsing and validating the XML documents need to be separated. This study focuses on constructing a separate XML document validator and validating XML documents against the defined XSD rules. A Java program is used to perform this experiment. Furthermore, the critical differences between XSD and DTD are also mentioned.